Intergenerational transmission of World War II family historical memories of the Resistance. Issue 3 (24th October 2020) - Cordonnier, Aline; Bouchat, Pierre; Hirst, William; Luminet, Olivier
Abstract : Collective memory of historical events can be transmitted across generations not only through cultural memory but also through communicative memory; that is, transmitted by people who have lived through these particular times. Yet, few studies have examined the temporal horizon of a particular type of communicative memory: family historical memories. In this article, we examine the intergenerational transmission of memories from the Second World War in families with an ancestor who resisted during the German Occupation. We interviewed 20 French‐speaking Belgian families over three generations. During these individual interviews, participants narrated an anecdote about their ancestor and the Resistance. Then, for the middle and youngest generations, we provided a short cue related to the story chosen by the oldest generation and enquired whether they could tell us the story in their own words. Memory transmission was analysed through two processes: retelling and recalling. Our main result revealed that there was a loss of details across generations, but not complete oblivion. We also found some instances of family myth transmitted across all generations. This study provides evidence that family historical memories fade away after a generation or two, even when these memories describe historical events deemed important for family and society.